1999
DOI: 10.1606/1044-3894.1475
|View full text |Cite
|
Sign up to set email alerts
|

Intervention and Supervision in Strengths-Based Social Work Practice

Abstract: Building social work practice on a foundation of client strengths is a classic theme that is currently the subject of renewed attention within the profession. Through the years, the literature on social work supervision has periodically proposed building supervision on a foundation of practitioners' achievements. This article will explore the commonality of these two themes: intervention based on strengths (rather than pathology) and supervision based on achievements (rather than problems). The pursuit of an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 16 publications
0
40
0
1
Order By: Relevance
“…Practice theories and models of supervision Suggestions by Cohen (1999) regarding a strengths-based perspective on supervision relate to the creation of facilitative environments as proposed by Coleman (2003) and discussed in the previous section. New theoretical developments also concur with a strengths-based perspective on supervision, in that this perspective is an integral part of a competence model of supervision, which is proposed to empower social workers (Engelbrecht, 2004).…”
Section: Functions Of Supervisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Practice theories and models of supervision Suggestions by Cohen (1999) regarding a strengths-based perspective on supervision relate to the creation of facilitative environments as proposed by Coleman (2003) and discussed in the previous section. New theoretical developments also concur with a strengths-based perspective on supervision, in that this perspective is an integral part of a competence model of supervision, which is proposed to empower social workers (Engelbrecht, 2004).…”
Section: Functions Of Supervisionmentioning
confidence: 99%
“…Her composition of an educational model, based on Perlman's (1967) problem-solving process and Kadushin's (1976) exposition of it, is a definitive, comprehensive, unique framework for holistic supervision practice. However, the philosophical and theoretical underpinning of this frame of reference and the compatibility with contemporary theoretical developments in social work, such as a strengths-based perspective (Cohen, 1999), competence model of supervision (Page & Stritzke, 2006) and an outcomes-based orientation (Lombard et al, 2003) are ambiguous. Be that as it may, Botha's (2002) particular notions of principles of adult education, educational techniques, styles and patterns as well as her expositions of an educational evaluation, programme and contract definitely withstand the theoretical developments of the times, as contemporary commentators such as Coleman (2003), Hawkins and Shohet (2006), Tsui (2005) and Lewis et al (2007) present the same notions, although their views are substantiated with altered, present-day terminology.…”
Section: Content Of Supervisionmentioning
confidence: 99%
“…This conceptualization of supervision was first documented in the 1976 book publication of Alfred Kadushin's Supervision in Social Work. The profound international influence of Kadushin's 32-year-old definition of supervision has been repeatedly acknowledged in subsequent publications on social work supervision (for example, Brown & Bourne, 1996;Bruce & Austin, 2000;Cohen, 1999;Cooper, 2002;Jones, 2004;O'Donoghue, 2003;Tsui, 2005). The enduring quality of this conceptualization of supervision is obvious in the latest edition by Kadushin and Harkness (2002), in which the only change by the authors was to identify that a supervisor could be female as well as male.…”
Section: Traditional Social Work Supervisionmentioning
confidence: 98%
“…Over the past 30 years, the development of social work supervision has been significantly influenced by the writings of Alfred Kadushin, Carlton Munson, and Laurence Shulman (Brown & Bourne, 1996;Bruce & Austin, 2000;Cohen, 1999;Cooper, 2002;Jones, 2004;O'Donoghue, 2003;Tsui, 2005). In their most recent supervision texts, Kadushin and Harkness (2002), Munson (2002), and Shulman (1993) have demonstrated that experiences of diversity, specifically gender, culture (usually referring to ethnicity), and race, can influence the supervisory relationship.…”
Section: Cultural Relevancy and The Pursuit Of Social Justice Within mentioning
confidence: 99%
“…The generative nature is promoted, collaborative to the relationship based on balance and co-construction in favour of the transfer of resources towards the client. Cohen (1999) proposes the approach of supervision of social services, starting from the professionals" strenghts (strenghts based supervision), similar with the strenghts based social work model. In the Romanian literature refering to supervision, a similar approach is developed by Ştefan Cojocaru (2007) under the name of appreciative supervision.…”
Section: Limits and Criticisms Of The Practice Of Supervising Social mentioning
confidence: 99%